Beyond cultural distance: Switching to a friction lens in the study of cultural differences - Shenkar, Oded (Journal of International Business Studies, 2012)
My 2001 article provided a critical review of one of the most popular constructs in international business, and in the management and business literature as a whole, namely cultural distance. It listed various illusions, implicit yet unsubstantiated and refutable assumptions that underpinned a construct set to capture the essence of cultural differences. The paper questioned the validity of the measure; the resultant findings obtained in such international business applications as foreign direct investment patterns, sequence, entry mode, and performance; and, ultimately, the wisdom of continuing the use of the measure and its underlying construct. In this retrospective, I review subsequent work that tested some of the original observations, the impact the article has had, and, in particular, how we can redirect research away from the static cultural distance paradigm toward the dynamic interaction of the actual entities that come into contact in international business.